2013
DOI: 10.1021/ac402332z
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Assessment on the Use of Magnetic Nanoparticles for Glycopeptide Enrichment

Abstract: Glycoproteomics represent the field of study of the dynamic changes occurring among glycoconjugates within the cellular compartments. Changes in glycosylation have been linked to various diseases, including metastatic carcinomas in which the 9 carbon sialic acid moiety has been shown to play a prominent role. The common method used to study these aberrant changes most often includes a mass spectrometer at some stage in the workflow. However, serum samples contain many proteins which inhibit the analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 92 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…Elution of glycopeptides can be achieved by increasing the content of water in the mobile phase. Based on hydrophilic interactions and weak anion exchange principles, a recent application uses amine-functionalized magnetic nanoparticles with greater surface area to selectively enrich sialylated glycopeptides (38). Zwitterionic-HILIC (ZIC-HILIC), a variation of HILIC that uses zwitterions as stationary phases, has better separation efficiency for glycopeptides because additional ion-pairing effects exist in the separation process (39,40).…”
Section: O-linked Glycosylationmentioning
confidence: 99%
“…Elution of glycopeptides can be achieved by increasing the content of water in the mobile phase. Based on hydrophilic interactions and weak anion exchange principles, a recent application uses amine-functionalized magnetic nanoparticles with greater surface area to selectively enrich sialylated glycopeptides (38). Zwitterionic-HILIC (ZIC-HILIC), a variation of HILIC that uses zwitterions as stationary phases, has better separation efficiency for glycopeptides because additional ion-pairing effects exist in the separation process (39,40).…”
Section: O-linked Glycosylationmentioning
confidence: 99%
“…Methods based on hydrazide chemistry have been reported, exploiting oxidized cis-diol interactions [14,15], and other protocols focus on the capture of glycans through boronic acid interactions [16] or aniline groups functionalized to magnetic nanoparticles [17,18]. Hydrophilic interaction liquid chromatography (HILIC) approaches have shown to be simple, fast, and efficient relative to reversed-phase approaches for glycopeptide enrichment [19][20][21][22]. Much emphasis has been placed around the design of niche Bglyco-modified^columns usable under HILIC conditions including Bclick saccharides^onto polymer beads [23], silica beads [24,25], and magnetic nanoparticles [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the loading capacity of CMCH was not optimized, the amount of digest loaded, 25 mg, was well within the recommended maximum load for EMD ( [36], as well as optimization of isolation of glycopeptides from magnetic nanoparticles [34], and also from optimization of glycopeptide enrichment using cellulose [16], it was found that a ratio of approximately 7:3 is required for elution. If RP is used, approximately 30% ACN in water is needed to elute the bulk of glycopeptides, whereas by HILIC, glycopeptides will elute with 30% H 2 O in ACN.…”
Section: General Considerationsmentioning
confidence: 80%
“…However, as the CMCH beads were utilized according to HILIC protocols developed in our laboratory [16,34] and as they dramatically enrich glycopeptides, HILIC interactions are deemed to play an important role in glycopeptide enrichment. As for the WAX process, the amine on chitosan is proposed to interact with negatively charged sialylated species, as it can explain the more efficient enrichment of sialylated glycopeptides than seen using the EMD process.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation